Effects of Annona muricate Extract on Short Chain Fatty Acid Level of Colorectal Cancer Patients - Lili Indrawati; Purwantyastuti; Murdani Abdullah; Ingrid S Surono (Majalah Kedokteran UKI, 2020)
Annona muricata leaves contains phytochemical substances, such as alkaloids, tannins, flavonoids, saponins, anthraquinones and cardiac glycosides, ellagic acid, triterpenoids, β- sitosterol. Polyphenols are considered to be potential in providing health benefits via modulation the gut microecology. Alteration of the gut microbiota composition can be achieved by consuming of flavonol-rich foods that exerting prebiotic-like effects. Short chain fatty acids (SCFA) that are produced from highly fermentable fibers is considered to be protective against colon cancer. Subjects were assigned consecutively into two group: ethanolic extract of A. muricata, and maltose as placebo. Ssupplementation was conducted for 8 weeks in a capsule. SCFA level assessment was conducted at baseline and the end of the study period. Gas liquid chromatography was used to determine concentration of butyrate. Fiber intake was measured using food record. Concentrations of fecal butyrate levelwas not significantly different between Fraction of A. muricata water extract that is soluble in ethanol (FAMSE) and placebo (p=0.854). Level of others SCFA were also not significantly different. The low fiberintakeisconsistent with the finding on fecal butyrate concentration, as shown by no significant increase in both groups. There is no statistically significant effect of supplementation with ethanol-soluble fraction of A muricata leaves water extract on fecal SCFA level of colo rectal cancer (CRC) patients, andin line with fiber intake below recommended daily allowance throughout the study period. Keywords: phytochemical substances, fiber intake, gut microbiota Abstrak Daun sirsak (Annona muricata) mengandung senyawa fitokimia seperti alkaloid, tanin, flavonoid, saponin, antraquinon, cardiac glycosides, ellagic acid, triterpenoid, dan β-sitosterol. Polifenol memiliki potensi yang baik dalam kesehatan dengan cara memodulasi mikro-ekologi usus. Komposisi microbiota usus dapat berubah dengan cara mengkonsumsi makanan yang banyak mengandung flavonol yang memberikan efek seperti prebiotik. Asam lemak rantai pendek yang dihasilkan dari fermentasi tinggi serat dapat mencegah terjadinya kanker kolon. Subyek penelitian dibagi menjadi dua kelompok secara berurutan, yaitu ekstrak etanol Annonamuricata dan maltosa sebagai plasebo. Pemberian suplemen dilakukan selama 8 minggu dalam bentuk kapsul. Pengukuran kadar asam lemak rantai pendek dilakukan pada awal dan akhir masa studi ini. Pengukuran kadar asam butirat dilakukan dengan kromatografi gas. Asupan serat diukur berdasarkan catatan makanan. Konsentrasi kadar asam butirat pada feses tidak berbeda signifikan dengan fraksi ekstrak air Annona muricata yang larut di dalam etanol dan plasebo (p=0.854). Kadar dari asam lemak rantai pendek lainnya juga tidak berbeda nyata. Asupan serat yang rendah sejalan dengan pengukuran kadar asam butirat di feses yang menunjukkan tidak ada peningkatan secara signifikan pada kedua kelompok. Tidak terdapat pengaruh yang signifikan suplementasi dengan fraksi larut etanol ekstrak air daun Annona muricata pada konsentrasi asam lemak rantai pendek feses dari pasien kanker kolon dan hal itu sejalan dengan asupan serat dibawah rekomendasi harian yang dilakukan selama masa studi ini. Kata kunci: fitokimia, asupan serat, microbiota saluran cerna